A study - Incidence and pattern of musculoskeletal injuries among patients attending the emergency of tertiary health care center in Central India - Ashish Anand Gupta; Santosh Kumar Mishra; Suresh Uikey; Deepak Maravi (Journal of Orthopaedic Diseases and Traumatology, 2019)
Introduction: Trauma is the major cause of death and disability in developing country, is responsible for more years of life lost than most human diseases. This study aims to establish the value of a trauma registry by measuring, monitoring, and analyzing etiological factors of common musculoskeletal injuries caused due to several forms of trauma. Materials and Methods: This study has been conducted retrospectively. The patients attending the emergency department in tertiary care hospital were included in this study. Personal data and pattern of injuries sustained were extracted from the casualty admission register of emergency department and trauma unit, case records, and operation records. Results: A total of 6574 injured patients were seen in the emergency department. The most common injury was bony injury (65.38%, n = 4298) and soft-tissue injury 34.62% (n = 2276) and the most common sites were lower limbs in 41.39% of cases, amputation/crush injury in 7.82%, and 32.03% of cases (n = 1377) were of compound fractures. The most common soft-tissue injury was lacerated wound 45.21%. Most commonly associated injury was the head injury in 5.53% of cases. Maximum cases were in the age group of 30-59. Conclusion: Fractures were the most common pattern of injuries frequently associated with other injuries, especially head injuries, particular age group, and time period need special attention, and we need more such institutes near highways.